Corrosion in Molten Salts for Solar Thermal Power. (June 2021) - Summers, Kodi; Chidambaram, Dev
Abstract : Global energy needs continue to grow steadily with increasing population and standard of living. While fossil fuels have been a major source of our energy, they are no longer favorable due to their greenhouse gas emissions and atmospheric pollution; the development of carbon-free sources of energy is crucial. Solar energy promises unlimited amounts of emissions-free energy but suffers from intermittency issues that require expensive secondary energy storage systems to act as baseload power. A thermal energy storage (TES) system can store heat and provide a continuous source of power. Concentrated solar power (CSP) is carbon-free and can ideally be combined with a TES system to provide continuous power. These combined systems operate by focusing a large area of sunlight onto a receiver that contains a TES material to convert the sunlight into thermal energy.